Selective-enrichment as a Tool to Obtain Microbial Degrading Consortia for the Remediation of Pesticide Residues - Rodríguez Rodríguez, Carlos E. (2021)
Inadequate disposal of pesticides during their extensive use in agricultural practices may result in soil, surface, and groundwater pollution. These agrochemicals affect a wide variety of non-target organisms, and their presence in the environment produces significant toxicological disturbances at acute and chronic levels. The continuous exposure of soils to pesticides strongly selects bacteria with the capacity to tolerate or even degrade these pollutants, an ability that can be exploited for bioremediation purposes. During a selective-enrichment process, an environmental sample, such as soil pre-exposed to pesticides, is repeatedly exposed to a xenobiotic in order to obtain microbial consortia or individual isolates with the potential capacity to remove the target pollutant. This chapter analyzes methodological strategies and problems related to pesticide selective-enrichment processes aimed at biodegradation of agrochemicals. The performances of different approaches employed for the application of the isolated consortia are discussed.